Opting Out of Maxim in Quora Q&A Social Media - Ammar Rasyid; Zuindra Zuindra; Mayasari Mayasari (Pusat Riset dan Inovasi Nasional, 2024)
Researcher investigate how to be able to carry out conversations efficiently and effectively in computer-based media using Grice's cooperative principle theory. Researcher use the Qualitative method. The researcher took one of the questions in Quora Indonesia